Assessing young gymnasts’ dynamic posture : a comparison of methods - Jurak, Ivan, psihoterapeut (Array, 2020)
Functional Movement Screen is an established method of assessing dynamic posture of athletes. Validity and reliability of FMS as a screening tool is debated and one of the foremost criticism is directed at its subjectivity. To the authors’ knowledge, there is no previous research using Kinovea to precisely assess FMS scores. 10 young competitive gymnasts (4 female and 6 male) were included in this study. The participants were scored by an experienced FMS assessor on site as per standard FMS protocol. Afterwards, the same participants were scored again using Kinovea to achieve more objective measurements. Wilcoxon Signed Rank Test for FMS scores versus FMS-Kinovea scores identified FMS test no. 1 (Deep Squat) as significantly different. The median score of Deep Squat assessed on site was 2 (mean value: 2.1), while that same test, scored with Kinovea, had the median score of 1 (mean value: 1.2). Paired Pitman-Morgan test for equality of variances was used to test the dispersion of scores. None were shown to be statistically significant, however, overall FMS score was near significance threshold implying that there is a difference although our power of study was too low probably due to low sample size. We detected significant difference in the scores of Deep Squat test, which is not surprising since it is the most complicated test to asses due to a large number of variables the assessor must evaluate.